Transitivity of President Jokowi's Speech Text at the G20 Event: Systemic Functional Linguistics Study - Siska hardiyanti; Irma Setiawan; Nurmiwati Nurmiwati; Fatmala Sari Oktaviani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Using SFL analysis, this study seeks to describe the transitivity elements of Joko Widodo's speech at the G20 Summit. Through this research, it is hoped that insight will be gained and research development will be enhanced in the field of transitivity analysis contained in a text or similar material, and this research will then serve as a reference or source of information for future researchers. There are both spoken and written varieties of spoken language. Speech is one manifestation of oral communication. Empirical, practical, and theoretical phenomena constitute the primary foundation of research-based reasoning. This study employs a qualitative descriptive method and simple quantitative reasoning to provide a more comprehensive understanding of the quantity and presentation of tabular data. The data being analyzed is spoken data that is subsequently transcribed into words, phrases, clauses, and phrase groups. The data source is an audio-visual recording of Jokowi's speech obtained from the YouTube page of KompasTV.com. The method of data acquisition employs the listening technique, which is supported by the note-taking technique. In presenting data analysis, researchers employ general methods. The findings revealed that the types of processes detected in the data were mental, relational, behavioral, and verbal, with material processes dominating in appearance. Participant I and Participant II were discovered as humans and abstracts, respectively. The types of circumstances discovered took the form of extent, cause, matter, and function, and the manner of circumstance appearance predominated.